A Janus Separator for Inhibiting Shuttle Effect and Lithium Dendrite in Lithium−Sulfur Batteries. Issue 4 (9th March 2022) - Xiao, Ru; Yang, Shan; Yu, Tong; Hu, Tianzhao; Zhang, Xiaoyin; Xu, Ruogu; Wang, Yaozu; Guo, Xiaodong; Sun, Zhenhua; Li, Feng
Abstract: Invited for this month's cover picture is the group of Feng Li and Zhenhua Sun. The cover picture shows a conceptualized lithium−sulfur battery assembled with a Janus separator based on La2 Zr2 O7− x nanotubes with surface oxygen vacancies, in which the shuttle behavior of polysulfide is blocked by adsorption and catalysis effects, and uniform lithium (Li) deposition is achieved by fast free Li + transfer. Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the full text of the Research Article at 10.1002/batt.202100389 . Abstract : "La2 Zr2 O 7−x nanotubes with surface oxygen vacancies (OV–LZO) were fabricated as a Janus separator coating for lithium−sulfur (Li−S) batteries, which constructed a polysulfide adsorption and catalysis network at the cathode/separator interface and a fast Li + transport network at the anode/separator interface to tackle the shuttle effect and Li dendrite issues. The main body of the cover graphic shows the Li−S battery conceptualized in this work. The effect of the OV–LZO‐based Janus separator is embodied concretely. Taking the universe as the background, the schematic profile of the Li−S battery constitutes a satellite‐like pattern, which reflects the broad application prospect…." Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Research Article on 10.1002/batt.202100389 .